2017
DOI: 10.1039/c7dt02072d
|View full text |Cite
|
Sign up to set email alerts
|

Structure and reactivities of rhenium and technetium bis-arene sandwich complexes [M(η6-arene)2]+

Abstract: Sandwich complexes are important building blocks in medicinal inorganic chemistry for group 6 and 8 elements but are almost unknown for the manganese triad. We present the syntheses and full characterization of the mixed-arene Tc sandwich complexes [Tc(η-hmbz)(η-CH-NH)](PF) and [Tc(η-hmbz)(η-CH-Br)](PF). Both comprise functionalities for conjugation to targeting molecules or for being included as substructures in pharmaceutically active lead compounds. Since η-benzene ligands are too stably bound to be replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 73 publications
3
47
0
Order By: Relevance
“…In the past few years, we developed synthetic strategies towards new [Re( 6 -C6R6)2] + and [ 99(m) Tc( 6 -C6R6)2] + sandwich complexes. [14][15][16][17][18] Similar to other [M( 6 -C10H8)2] bis-naphthalene complexes (M = Cr, Mo), [19][20][21] coordination of the naphthalene ligands to the Re I center is comparably weak in [Re( 6…”
Section: Resultsmentioning
confidence: 87%
“…In the past few years, we developed synthetic strategies towards new [Re( 6 -C6R6)2] + and [ 99(m) Tc( 6 -C6R6)2] + sandwich complexes. [14][15][16][17][18] Similar to other [M( 6 -C10H8)2] bis-naphthalene complexes (M = Cr, Mo), [19][20][21] coordination of the naphthalene ligands to the Re I center is comparably weak in [Re( 6…”
Section: Resultsmentioning
confidence: 87%
“…The symmetry of all NMR spectra and therefore the free rotation around the rhenium axis is found for all [Re(arene) 2 ] + synthesized by our group so far. [5][6][7]16,17,27 Pyridines are prototypical ligands in many catalytic processes, e.g. for proton reduction in photocatalysis.…”
Section: Conjugation Of Ligands To Complexes 2a + -3b +mentioning
confidence: 99%
“…In contrast to its neighbouring elements, we found that [Re(η 6 -C 6 H 6 ) 2 ] + type complexes are remarkably stable. 4,5,16 For instance, [Re(η 6 -C 6 H 6 ) 2 ] + does not decompose or lose benzene rings even when heated to 160°C or when irradiated with UV light. [Re(η 6 -C 6 R 6 ) 2 ] + offers structural flexibilities in three dimensions as depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with isotopes 186 and 188 of its heavier homolog rhenium ( 186/188 Re), it represents one of the first "theranostic pairs" for nuclear medical diagnosis and therapy [6]. Recently, a conceptual extension of the "theranostic pair" Tc/Re was described by the combination of a 99m Tc-based bio-mimetic with its organometallic but non-radioactive rhenium homologue [7]. The rhenium complex should be therapeutically active through its structure, while the 99m Tc homologue allows for visualizing the pharmacology.…”
Section: Introductionmentioning
confidence: 99%